32.1k views
4 votes
Composite functions 65 points helpppppp

Composite functions 65 points helpppppp-example-1

2 Answers

6 votes

Answer:


4√(x+2) - 6

Explanation:

f(g(7)) = f(sqrt(x+2))

=4(sqrtx+2) - 6)

=
4√(x+2) - 6

User Sergei Tachenov
by
5.7k points
4 votes

Answer:


(f \circ g)(7)=6

Explanation:

Given functions:


\begin{cases}f(x)=4x-6\\g(x)=√(x+2)\end{cases}

(f o g)(x) is a composite function.

Composite functions are when the output of one function is used as the input of another.

Therefore, the given composite function (f o g)(7) means to substitute the function g(x) when x=7 in place of the x in function f(x).


\begin{aligned}\implies (f \circ g)(7)&=f[g(7)]\\& = f(√(7+2))\\&=f(√(9))\\&=f(3)\\&=4(3)-6\\&=12-6\\&=6\end{aligned}

User Gemmakbarlow
by
5.4k points